The Influence of Sales Promotion, Perceived Product Quality and Hedonic Perception on Consumers’ Purchase Intention - The Moderating Effect of Brand Awareness - Gu, Yi Chen (2019)
Because of the growth in exercise trend in Taiwan, not only for people who have begun to view the sports activities as an important issue and pay more attention on health and living in a higher quality life. Based on this trend, the sports markets in Taiwan have seized an opportunity to establish their markets. Therefore, the main purpose of this research is to examine the vital factors that will affect the consumer’s attitude towards sporting products and their purchase intention in Taiwan. This research used online survey to distribute to 300 respondents and enrol them participating in the questionnaire. The result revealed that sales promotion, perceived product quality and hedonic perception have a positive significant relationship to the consumers’ attitude towards sporting products. Also, the brand awareness has influence the correlation between consumers’ attitude towards sporting products and purchase intention. Therefore, according to the result, this research not only can provide important information of consumers’ attitude towards sporting products for enterprises such as how do consumers they view the sporting products which are in the sales promotion or how do sporting companies they strengthen their brand image and store image to allow consumers aware of their brand when their brand shows up in front of them, but also help them to build up a greater competitive marketing strategy throughout the sports markets.